Should we pay attention to recombinant norovirus strain GII.P7/GII.6?. Issue 3 (May 2019) - Dong, Xiaogen; Qin, Meng; Wang, Zhao-e; Yang, Xiaoxing; Wu, Qingrui; Feng, Huiru; Wei, Xiuxia; Yu, Hong; Li, Jinsong; Li, Jie
Abstract: Background: Recombinant norovirus strain GII.P7/GII.6 has been circulating in Asia and around the world for at least 20 years, but has been responsible for relatively few outbreaks. Methods: We used statistical analyses, real-time reverse transcription – PCR, and genome sequence analyses to investigate an outbreak of gastroenteritis, identifying the pathogen, the risk factors associated with the outbreak, and the molecular features of GII.P7/GII.6 strains. Results: An outbreak of gastroenteritis was reported at a school involving 12 students and lasting 6 days, from September 13 to September 18, 2017. Epidemiological studies suggested that norovirus was transmitted from person to person and not via contaminated food or drinking water in this outbreak. Using a sequence analysis of the junction region between open reading frames 1 and 2, the pathogen was identified as a recombinant norovirus (strain GII.P7/GII.6). The full-length genome of the outbreak strain shared 86%–97% identity with those of other GII.P7/GII.6 strains. Phylogenetic trees were constructed from partial open reading frame 1 (ORF1) and ORF2 sequences from the outbreak strain and GII.P7/GII.6 norovirus sequences available in GenBank. On the ORF1 tree, the partial sequences of ORF1 were grouped into cluster A (with GII.6), cluster B (with GII.7), and a separate cluster (C), based on the GII.6 and GII.7 reference strains. The ORF2 tree showed all GII.P7/GII.6 strains formed a cluster together with GII.6 strains. Amino-acid substitutions and insertions/deletions were common in the capsid protein, especially in it's P2 and P1 domains. The outbreak was controlled within several days using appropriate measures. Conclusions: Because it may play a prominent role in future outbreaks, recombinant norovirus strain GII.P7/GII.6 should be monitored with routine surveillance.